The comprehension and production of verbal passives by Italian preschool-age children. (1st September 2015) - VOLPATO, FRANCESCA; VERIN, LAURA; CARDINALETTI, ANNA
ABSTRACT: This paper investigates the comprehension and the production of passive sentences in Italian-speaking children (aged 3 years, 4 months to 6 years, 2 months) analyzing both the variables observed in previous studies on other languages (verb type and presence of the by -phrase) versus an Italian-specific variable: the use of auxiliary venire "to come." Because Italian venire is only possible in verbal passives, this property is crucial to determine whether children have full competence of the (verbal) passive structure. The high percentage of accuracy in the comprehension of sentences containing venire suggests that the eventive passive interpretation is fully available in child language, even in 3- to 4-year-old children. Moreover, young children produce passive sentences with either auxiliary venire or essere "to be, " also adding the by -phrase, thus proving unambiguously that children control verbal passive sentences from very early on.